MINAT MASYARAKAT MENYEKOLAHKAN ANAKNYA KE SEKOLAH MENENGAH PERTAMA (SMP) DAN MADRASAH TSANAWIYAH (MTs) DI KECAMATAN SEMIDANG GUMAY KABUPATEN KAUR - Dasman Yanuri (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2016)
Abstract: The background of this research on the public interest and the factor less or high interest of Reviews their parentssend children to school (SMP) and MTs (MTs) in District Semidang Gumay Kaur regency. The problems of this study are1. What are the reasons parents send Reviews their children to MTs? 2. What are the reasons parents send Reviews theirchildren to school (SMP), 3. Do We Become less a factor or high interest of parents to Reviews their children send schoolat junior schools and junior high schools in the District Semidang Gumay Kaur Regency? this study used qualitative researchmethods, the data collection techniques used were interviews, observation and documentation. The usefulness of this study isto describe the public interest to send Reviews their children to junior high and into Islamic. Reviews These results indicatethat, reasons parents send Reviews their children to madrassas tsanawiyah Because madrassas are educational apply betweenreligious knowledge and general science are balanced, close to the tourist Attractions are within easy reach, went along withhis brother who had entered into the madrassa tsanawiyah, and Reviews their destination that parents of children Becomesmart kid coveted by parents. Sekoah madrassa student tsanawiyah lower interest, this is evidenced by the number of studentsis less. The reason parents send Reviews their children to school (SMP) for the school environment closer to home, hisown interests. Reviews their interest to parents of children to be a smart kid and useful for religious homeland. Motivatestudents to school at Junior High School (SMP) is higher, it can be seen from the number of students more. Factors less orhigh interest of parents and children to school or madrassa tsanawiyah Junior High School (SMP) Came from within thestudents Themselves and the factors encouragement from parents.